FINANCIAL RESOURCE MANAGEMENT SKILLS REQUIRED BY SECONDARY SCHOOL PRINCIPALS IN CROSS RIVER STATE (Journal of Association of Educational Management and Policy Practitioners, 2024)
This study focused on financial resource management skills required by secondary school principals in Cross River State. The study investigated the skills needed of secondary school principals in two specific areas namely budgeting process and auditing of school accounts,. Two corresponding research questions and null hypotheses were formulated to guide the study.. The population of the study consisted of two hundred and twenty-one (221) principals of secondary schools in Cross River State. The entire population was used in the study and as such there was no sampling. The researchers developed questionnaire tagged Financial Resources Management Skills Required by Secondary School Principals in Cross River State (FRMSRSSPQ) was used to elicit responses from the subjects. The instrument was validated The reliability of the instrument was determined using Cronbach Alpha technique which yielded a reliability coefficient of 0.78. Mean (x) and standard deviation (SD) were used to answer the research questions while t–test statistics was used to test the null hypotheses at 0.05 level of significance. The findings showed that principals of secondary schools highly needed skills in: budgeting process and auditing of school accounts. There was also no significant difference in the mean ratings of male and female principals on skills needs of principals in the two areas studied. Based on the findings of the study, the researcher recommended among others that the Cross River State government, under the State Ministry of Education, should regularly organize intensive workshops, seminars, and conferences on skills requirements of principals in financial resource management in secondary schools